THE INFLUENCE OF OVERCONFIDENCE AND FINANCIAL LITERACY ON INVESTMENT DECISIONS AMONG GENERATION Z - Elsa Ramelpa Silaban; Agus Zainul Arifin (International Journal of Application on Economics and Business, 2025)
This study aims to examine the influence of overconfidence and financial literacy on investment decisions. The study involves 126 respondents, consisting of Generation Z individuals in the Jabodetabek area, who have experience in investing, whether currently active or previously involved in investments in instruments such as stocks, mutual funds, deposits, and foreign exchange, through both digital platforms and traditional methods. The Partial Least Square method was used to analyze the relationship between overconfidence and financial literacy on investment decisions. The results reveal that overconfidence and financial literacy have a positive impact on the investment decisions of Generation Z in Jabodetabek. This study provides a new perspective in understanding the psychological factors influencing investment decisions among Generation Z, particularly in the Jabodetabek area, and can be utilized to help them make more rational and informed investment decisions. Furthermore, the findings are expected to raise awareness among Generation Z regarding the importance of adequate financial literacy and managing self-confidence levels proportionally to avoid making poor investment decisions due to psychological biases. This study is the first attempt to use Generation Z subjects in the Jabodetabek area to evaluate their investment decisions within the context of financial instruments such as stocks, mutual funds, deposits, and foreign exchange in the Indonesian market.